How Cognitive Styles Shape Creative Mathematical Thinking - Dian Septi Nur Afifah; Grafika Saraswati; Silfia Hayuningrat (Riemann: Research of Mathematics and Mathematics Education, 2026)
Creative thinking is widely recognized as a core component of higher-order thinking in mathematics education; however, its development among Indonesian students remains a persistent challenge, as reflected in large-scale international assessments such as PISA 2018. Differences in students’ cognitive styles particularly reflective, impulsive, and slow-inaccurate styles are assumed to shape cognitive processing and mathematical problem-solving performance, yet empirical evidence remains limited. This study aims to examine students’ creative thinking ability in mathematical problem solving from the perspective of these cognitive styles. Employing a qualitative descriptive approach, the participants were eighth-grade students from SMP Negeri 2 Sumbergempol Tulungagung, classified using the Matching Familiar Figure Test (MFFT). Data were obtained through problem-solving tests and semi-structured interviews and analyzed through methodological triangulation. The findings indicate that students with reflective cognitive styles exhibit a high level of creative thinking, characterized by fluency, flexibility, and originality. In contrast, students with impulsive and slow-inaccurate cognitive styles demonstrate moderate creative performance, predominantly reflected in elaborative responses. These results highlight the need for differentiated instructional strategies that align with students’ cognitive characteristics. The study contributes to the growing body of literature on cognitive style-based instruction and offers pedagogical insights for fostering creative thinking in mathematics classrooms.